Institutions, financial development, and small business survival: Evidence from European emerging markets - Ichirō Iwasaki; Evžen Kočenda; Yoshisada Shida (Leibniz-Institut für Ost- und Südosteuropaforschung (IOS), 2021)
In this paper, we traced the survival status of 94,401 small businesses in 17 European emerging markets from 2007-2017 and empirically examined the determinants of their survival, focusing on institutional quality and financial development. We found that institutional quality and the level of financial development impact the survival probability of the researched SMEs in statistically significant and economically meaningful ways. The evidence holds even when we control for a set of firm-level characteristics such as ownership structure, financial performance, firm size, and age. The findings are also uniform across industries and country groups and robust beyond the difference in assumption of hazard distribution, firm size, region, and time period.
urn:nbn:de:101:1-2021022308515363136936
Keywords: C14; D02; D22; G33; M21; 330; small business; institutions; financial development; survival analysis; European emerging markets